Symptoms and growth components in feijoa (Acca sellowiana [O. Berg] Burret) plants in response to calcium, magnesium and boron deficiencies - Buitrago, Sebastián; Leandro, Manuel; Fischer, Gerhard (Sociedad Colombiana de Ciencias Hortícolas-SCCH and Universidad Pedagógica y Tecnológica de Colombia-UPTC, 2023)
Nutrient deficiency symptoms are widely used to determine the nutrient demands of a crop and to clarify nutritional disorders, especially when they are nutrient specific. Until now, a calcium (Ca), magnesium (Mg) and boron (B) deficiency experiment has not been carried out on feijoa, and diagnostic symptoms have not been described. For this reason, 9-months-old ‘Quimba’ feijoa plants were studied using the missing nutrient method. A modified Hoagland and Arnon solution was applied for each treatment, leaving out one element in each treatment. The treatments were: (1) complete fertilization (control); (2) complete fertilization -Ca; (3) complete fertilization -Mg; (4) complete fertilization -B; and (5) without fertilization (negative control). Deficiency symptoms in the plants were described, and photographic records were made. The Ca deficiency was noted early in the shoot tips and later in fully-expanded, young leaves. The Mg-deficiency was observed in older and fully-expanded leaves, mainly as interveinal chlorosis, while the B deficiency generated a variety of symptoms, interveinal and total chlorosis in fully and not fully-expanded leaves and a mosaic of symptoms in adult leaves. For the growth components, the Mg deficiency reduced the number of apical shoots, while the Ca- and Mg-deficiencies reduced the seedling growth rate significantly. For future experiments, the authors suggest an experiment period longer than 102 d to achieve more conclusive results.